Book review: Murphy, Gregory L. Categories we live by: how we classify everyone and everything - Elena Maceviciute (Information Research: An International Electronic Journal)
Murphy, Gregory L. Categories we live by: how we classify everyone and everything. Cambridge, MA: The MIT Press, 2024. x, 175 p. ISBN 978-0-262-54703-1